2022
DOI: 10.3390/ani12121475
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure of Broodstock to Dietary Soybean Meal Affect Its Utilization in the Offspring of Zebrafish (Danio rerio)?

Abstract: Nutritional programming (NP) is a concept in which early nutritional events alter the physiology of an animal and its response to different dietary regimes later in life. The objective of this study was to determine if NP via broodstock with dietary plant protein (PP) has any effect on the gut microbiome of the progeny fish and whether this modified gut microbiome leads to better utilization of PP diet. The experiment consisted of four different treatments as follows: (1) progeny that received FM diet obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…Studies of NP with a similar experimental design to what we have described here have shown no microbiota difference throughout the feeding trial and thus concluded that NP had not impacted the gut microbiota [ 45 , 46 , 49 ]. These studies proposed that the environmental factors represented by the RAS water tank abiotic conditions, including pH, temperature, and salinity, may outweigh the effects of NP and dietary protein sources.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Studies of NP with a similar experimental design to what we have described here have shown no microbiota difference throughout the feeding trial and thus concluded that NP had not impacted the gut microbiota [ 45 , 46 , 49 ]. These studies proposed that the environmental factors represented by the RAS water tank abiotic conditions, including pH, temperature, and salinity, may outweigh the effects of NP and dietary protein sources.…”
Section: Discussionsupporting
confidence: 61%
“…Nutritional programming has been employed to reduce the adverse effects of plant-derived dietary ingredients in commercial Atlantic salmon feed formulations, but the mechanisms behind NP effects, required to determine appropriate intervention timing and delivery methods, are as yet unclear [ 25 , 46 ]. Previous studies investigated whether NP modulated the gut microbiota and if such modulation could be coupled with fish performance [ 25 , 46 49 ]. In this study, we compared the effects of first feeding with a plant-based diet vs. a traditional marine-based diet on the developmental microbial composition and diversity of the intestine in Atlantic salmon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations